PENGARUH MEDIA VIDEO ANIMASI INTERAKTIF BERBASIS POWTOON TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR PADA MATERI BILANGAN CACAH - Abdulloh Ibnu Mubaroq; Dhina Cahya Rohim; Devy Aufia Abshor (STKIP Subang, 2026)
The low learning outcomes of students in whole number material, particularly in addition and subtraction. Students experienced difficulties in understanding counting concepts and showed low engagement during lessons. This research aimed to examine the effect of Powtoon-based interactive animated videos on students’ mathematics learning outcomes, measure the improvement in their achievement, and analyze their responses to the learning process. A quantitative approach with a quasi-experimental nonequivalent control group design was applied. The sample consisted of 30 students in class II A as the experimental group and 29 students in class II B as the control group. Data were collected through pretests, posttests, questionnaires, interviews, and documentation. Statistical analysis included normality and homogeneity tests, paired sample and independent sample t-tests, and N-Gain analysis using SPSS. The findings revealed that the use of Powtoon-based interactive animated videos significantly improved students’ mathematics learning outcomes. The experimental group achieved higher posttest scores with a moderate-to-high N-Gain level